Lembaga Penyelenggara dan Pengawasan Pemilihan Umum di Indonesia - Moh. Hudi; Restu Syamsariatullah; Nurul Hani; Ririn Novia Hidayati (Universitas Islam Darul Ulum Lamongan, 2023)
The 1945 Constitution explains that sovereignty is in the hands of the people and is implemented according to the Constitution. The embodiment of sovereignty in the hands of the people means that those who have the right to choose the leader or government are the people and as a logical consequence those who choose are the people, so the leader must be responsible to the people. In choosing leaders, the people need an institution, in this case the general election commission which is regulated in the 1945 Constitution. The task of the General Election Commission is to carry out or hold general elections to elect leaders. So that election results can be carried out directly, publicly, freely, confidentially, honestly and fairly, supervision is needed, in this case the general election supervisory body. On this basis, the results of the general election produce leaders who can properly carry out their duties in accordance with the needs of the people they represent.